Parasitic Hymenoptera Diversity and Abundance in Fruit Orchard Ecosystems in Muzaffarpur Region of Bihar - Rani , Neha; Gupta, Archana; Mallick, Alpana; Kumari , Divyani (American Journal of Biology and Natural Sciences, 2025)
Fruit orchards serve as intricate agroecosystems where maintaining a balance between beneficial and harmful insect populations is critical for ensuring productivity and long-term sustainability. Muzaffarpur, a prominent fruit-producing hub in Eastern India, is celebrated for its significant litchi and mango output, substantially bolstering Bihar's fruit economy with its distinguished Geographical Indication tags, particularly for mangoes and litchis. This comprehensive year-long study is dedicated to exploring the diversity and ecological importance of parasitic Hymenoptera, with the aim of evaluating parasitoid biodiversity across the region's fruit orchards. The research identified a total of 14 species, each representing a unique genus from 7 families, through morning observations. Peak abundance was noted during the summer, post-monsoon, and winter seasons. The observed moderate diversity is likely influenced by intensive management practices, highlighting the necessity for strategies to enhance biodiversity. This pivotal research is essential for paving the way for biological control strategies, offering a resilient and eco-friendly alternative to chemical pesticides.